Perception of Taman Harapan Kolongan SDA Church Member towards Spiritual Growth in Covid-19 Pandemic Period - Kelendonu, Michael; Harwanto, Budi (8ISC Abstract Proceedings, 2022)
Christians’ spiritual growth ideally increases over time. However, the presence of the Covid-19 pandemic has brought an impact on church life. There have been some limitations to performing church ministry and mission. The church tried to find other methods and strategies to continue fulfilling them. For this reason, this research was conducted to find church members’ perceptions of their spiritual growth during the pandemic period. Applied to convenience sampling, the study involved 33 members of Taman Harapan Kolongan Seventh-day Adventist Church. To draw the proposed result, this study implemented descriptive statistics to find the mean score of the respondent perceptions. Understanding of ministry and mission during the pandemic, worship service engagement, church ministry involvement, and fellowship among the church members were analyzed. Based on the data analysis, the findings showed that church members’ perception of spiritual growth during the Covid-19 pandemic was high. The congregation felt the impact of Covid-19 on their spirituality. The research findings recommend that the church may continue to strengthen church services during the Covid-19 pandemic so that the congregation remains strong in God. Keywords : Spiritual growth, church members, church ministry, Covid-19